Réponses

Meilleure réponse !
2013-02-16T20:09:37+01:00

s=(2x+5)(2x-5) = 4x² -10x + 10x - 25 =4x² - 25

t=(x+1)(x+1)-(3x+1)(2x+2) = x² - 2x + 1 - 6x² -6x -2x - 2 = -5x² -10x - 1

u=(x-4)(2x+7)+(2x-3)(5-3x) = 2x² +7x-8x-28 + 10x-6x²-15+9x = -4x²+18x-36

v=(x+3)(x+5)-(-x-2)(3x+5)=x²+5x+3x+15+3x²+5x+6x+10=4x²+19x+25

 

En espérant t'avoir aidé.

2013-02-16T20:13:30+01:00
S= 4x^2-25 T=x^2+2x-6x^2-6x-2x-2 =-5x^2-6x-2 U=2x^2+7x-8x-28+10x-6x^2-15+9x^2 =5x^2+9x-43 V=x^2+5x+3x+15+3x^2+5x+6x+10 =4x^2+19x+25